Migration and Social Cohesion in the UK - Hickman, M. author. aut Link
VI, 232 p.
Keywords: Based on a flagship research project for the Joseph Rowntree Foundation's Immigration and Inclusion programme, this book argues that social cohesion is achieved through people (new arrivals as well as the long-term settled) being able to resolve the conflicts and tensions within their day-to-day lives in ways that they find positive and viable.